Teacher’s Code of Ethics: Implementation by Mathematics Teachers in Cirebon City and Regency - Lestiana, Herani Tri (JUPE : Jurnal Pendidikan Mandala, 2024)
A teacher must uphold the teacher’s code of ethics, both when carrying out professional obligations in the school environment or outside the school, so that he can carry out his duties and responsibilities as a professional teacher well. This research aims to (1) find out how the teacher code of ethics is implemented in SMP/MTs and SMA/MA/SMK in Cirebon Regency and City, and (2) find out the obstacles faced by teachers in implementing the teacher code of ethics. The method used in this research is a descriptive method with data collection using questionnaires, observation and interviews. The subjects of this research were 125 Mathematics teachers in SMP/MTs and SMA/MA/SMK in Cirebon Regency and City. The research results show that Mathematics teachers in Cirebon Regency and City have implemented the teacher code of ethics very well with average questionnaire scores of 4.62 and 4.52 respectively. Mathematics teachers in Cirebon Regency and City also show a very good category in implementing each aspect of the code of ethics, namely the relationship between teachers and students, with parents/guardians of students, with the community, with colleagues, and with their profession. Obstacles faced by teachers in implementing the teacher's code of ethics include (1) the diversity of students' characters and backgrounds in one class, (2) differences in educational patterns between parents/guardians and difficulties in communicating with parents/ student guardians, (3) a feeling of reluctance to remind teachers not to take actions that demean the dignity of the teaching profession, (4) lack of opportunities for some teachers to develop the quality of the teaching profession, and (5) communities seem indifferent and don't care about the development of education around them.